2008
DOI: 10.1177/0022487108328486
|View full text |Cite
|
Sign up to set email alerts
|

Video Annotation Tools

Abstract: While video has long been used to capture microteaching episodes, illustrate classroom cases and practices, and to review teaching practices, recent developments in video annotation tools may help to extend and augment teacher self-reflection. Such tools make possible the documentation and support self-analysis using verifiable evidence as well as to examine changes in development over time. Video annotation tools offer the potential to support both the reflection and analysis of one's own teaching with minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(59 citation statements)
references
References 15 publications
(14 reference statements)
0
52
0
7
Order By: Relevance
“…(Riesback, 1996, cited in Bennett et al, 2002 Annotation tools provide the means for students to actively label and index video cases. Examples of video used to present real-world cases for student annotation include pre-service education students analysing both video cases of experienced teachers' practice (Zottman et al, 2013) and school children tackling mathematical problems (Rich & Hannafin, 2009); and chiropractic students analysing chiropractic clinical episodes to stimulate clinical thinking processes (Colasante et al, 2014).…”
Section: Teaching Strategiesmentioning
confidence: 99%
“…(Riesback, 1996, cited in Bennett et al, 2002 Annotation tools provide the means for students to actively label and index video cases. Examples of video used to present real-world cases for student annotation include pre-service education students analysing both video cases of experienced teachers' practice (Zottman et al, 2013) and school children tackling mathematical problems (Rich & Hannafin, 2009); and chiropractic students analysing chiropractic clinical episodes to stimulate clinical thinking processes (Colasante et al, 2014).…”
Section: Teaching Strategiesmentioning
confidence: 99%
“…Capturing the voice, the behaviour and the movement of teachers and pupils in a powerful medium (Tochon, 2001) enables teacher trainees to view examples of authentic learning experiences. In fact, several studies (Harford & MacRuairc, 2008;Newhouse, Lane, & Brown, 2007;Rich & Hannafin, 2009;Rosaen, Lundeberg, Cooper, Fritzen, & Terpstra, 2008) have shown that digital video is a powerful means of facilitating critical reflection and furthering self-evaluation.…”
Section: Possible Methods Used For Reflective Thinkingmentioning
confidence: 99%
“…Son diversas las estrategias en las que se emplea la visualización de grabaciones de vídeo (Amobi, 2005;Gaudin y Charliès, 2015) y que han demostrado incrementar la reflexión de los profesores en formación y en ejercicio. Dicha reflexión se ve favorecida con el uso de herramientas que permiten focalizar el análisis ya que, de este modo, se ofrece la oportunidad a los profesores en formación de visualizar, analizar y perfeccionar su práctica docente antes, durante y después de su trabajo en el aula (Rich y Hannafin, 2009).…”
Section: Reflexión En La Formación Inicial Del Profesoradounclassified